Correlation Between Intracranial Arterial Calcification and Imaging of Cerebral Small Vessel Disease - Chen, Yuan-Chang; Wei, Xiao-Er; Lu, Jing; Qiao, Rui-Hua; Shen, Xue-Feng; Li, Yue-Hua (Frontiers in Neurology, 2019)
Background and purpose: Vascular calcification is part of the atherosclerotic process. Intracranial artery calcification is closely associated with cerebral small vessel disease (SVD). The present study aimed to investigate the distribution pattern of intracranial arterial calcification and its association with magnetic resonance imaging (MRI) markers of SVD in patients with acute ischemic cerebrovascular disease. Methods: Two hundred and seventy six consecutive patients with transient ischemic attack (TIA) or acute ischemic stroke who underwent both computed tomography (CT) angiography and MRI were enrolled in this study. Intracranial arterial calcium scores were divided into four severity grades based on the Agatston method. MRI was performed to assess cerebral infarction, white matter hyperintensities (WMHs), lacunes, cerebral microbleeds (CMBs), and enlarged perivascular spaces (EPVSs). Results: Intracranial artery calcification was present in 200 (72.46%) patients, with the highest prevalence in the internal carotid arteries (ICA) (64.8%). The severity of intracranial arterial calcification was associated with the presence of WMHs (P = 0.0001), lacunes (P = 0.0001), and CMBs (p = 0.005); however, there was no association between calcifications and the presence of EPVSs (P = 0.518). The adjusted odds ratios (ORs) of severe intracranial arterial calcification were: 2.747 for WMH (grade 1–2), 3.422 for WMH (grade 3), 2.902 for lacunes, 2.449 for CMB, 0.88 for EPVS (grade 1), and 0.295 for EPVS (grade 2–4). Conclusion: Intracranial artery calcification is common in patients with ischemic cerebrovascular disease and the intracranial carotid artery is most frequently affected. Intracranial arterial calcifications might be associated with imaging markers of SVD and are highly correlated with WMHs, lacunes, and CMBs. Quantification of calcification on CT provides additional information on the pathophysiology of SVD. Intracranial arterial calcification could act as a potential marker of SVD.